Identification of immune-related genes from kidney and spleen of turbot, Psetta maxima (L.), by suppression subtractive hybridization following challenge with Vibrio harveyi - Wang, Chunzai; Zhang, Xiao-Hua; Jia, A; Chen, Jixiang; Austin, Brian (Journal of Fish Diseases, 2008)
Suppression subtractive hybridization was used to investigate the response of turbot, Psetta maxima (L.), to Vibrio harveyi, by using a cDNA library constructed from artificially infected turbot kidney and spleen mRNA. Forty-nine expressed sequence tags were obtained. Several immune system genes were identified, including a major histocompatibility complex (MHC) class Ia gene and a heat shock protein 70 gene. Some signalling molecules were also present in the cDNA libraries, including src-family tyrosine kinase SCK, sgk-1 serine-threonine protein kinase and amyloid precursor-like protein 2. The full length of MHC class Ia cDNA was cloned from turbot cDNA by rapid amplification of cDNA ends polymerase chain reaction. The nucleotide sequence of turbot MHC class Ia has been submitted to GenBank with accession number EF032639. The turbot MHC class Ia cDNA has an open reading frame encoding 354 amino acids, and the deduced amino acid sequence of turbot MHC class Ia has 68%, 54%, 51%, 52%, 57%, 33%, 29% and 29% identities to those of olive flounder, medaka, rainbow trout, Atlantic cod, tiger puffer, chicken, mouse and human, respectively. Quantitative reverse transcriptase-PCR was performed for the MHC class Ia gene, and it was revealed that the expression level of the MHC class Ia gene in V. harveyi-challenged turbot increased to fourfold that of the controls.